Analisis Konten Instagram @Uinsu_Official sebagai Media Informasi Universitas Islam Negeri Sumatera Utara - Nabila, Nur’Aida; Tanjung, Muaz (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the Instagram account @uinsu_official as an information medium for Universitas Islam Negeri Sumatera Utara (UINSU). A qualitative approach with content analysis was employed to examine Instagram posts published between April and June 2025, selected through purposive sampling. Data were collected through non-participant observation and documentation of visual content, captions, hashtags, and audience engagement, including likes, comments, and shares. Data analysis involved data reduction, data display, and conclusion drawing. The findings indicate that @uinsu_official functions effectively as an institutional information medium by providing informative content, attractive visuals, and accessible information. However, several limitations remain, including incomplete information in some posts and limited interaction, as administrators did not respond to users’ questions in the comment section. The study concludes that @uinsu_official has served as an effective information medium for UINSU but requires improvements in information completeness and two-way communication to enhance the effectiveness of information dissemination.